Exploring the Use of Infographics to Alter Consumer Opinions and Perceptions of Sustainability within the U.S. Beef Industry - Gabriella F. Johnson; David S Martin; Jason T. Sawyer; Don Mulvaney (Journal of Applied Communications, 2025)
The meat industry faces increasing scrutiny over its environmental impact, animal welfare practices, and role in sustainable food systems, often fueled by misinformation and lack of consumer understanding. The purpose of this research was to explore the effectiveness of using infographics to change negative or misinformed opinions about the beef industry. Effective science communication strategies, such as evidence-based infographics, offer a promising approach to conveying complex agricultural topics in a visually engaging and accessible manner. These communication devices are effective in visually informing audiences and simplifying the messages; however, there is not a large body of literature on infographic use in agricultural education. A survey was conducted to gather participants’ subjective and objective knowledge about resource usage, their prioritization of sustainability issues to address, and their beef shopping habits. Participants then rated their agreement with statements about sustainability, grass-fed and conventional cattle, and hormone use. After viewing three infographics, they were reassessed on the same questions to determine any changes in opinions or knowledge. Results showed a significant increase in self-reported knowledge (p < .001) and positive increases in opinions and agreement on statements about sustainability in the beef industry (p < .001). Participants expressed lingering doubt about the hormone information and the over- or underinflation of statistics represented. Further research could include more specific infographics focusing on fewer topics to decrease information load and integrating more interactive elements into the infographics to increase participation and interaction.
Keywords: beef industry; consumer perceptions; infographics; sustainability